The Structure of State Ministries in Indonesia's Presidential System: Prohibition of Dual Positions for Deputy Ministers - Rahmat Saputra; Salha Marasaoly; Andika Adhyaksa (International Journal Labs, 2026)
This research aims to find out the extent of the effectiveness of the implementation of the ban on dual positions for Deputy Ministers in Indonesia. Deputy Ministers (Wamen) in the Indonesian government system were formed to assist the Minister to improve the effectiveness of state administration. This is in line with the provisions of Article 23 of Law Number 39 of 2008 concerning State Ministries, that Ministers and Deputy Ministers are prohibited from holding concurrent positions. However, in practice, this shows that there is several Deputy Ministers who are still holding dual positions. This research uses a normative research method with a legislative approach. The legal materials used in this study include primary legal materials consisting of relevant laws and regulations and legal documents, as well as secondary legal materials in the form of books, journals, and print and online media that are directly related to the research object. All these legal materials are collected through literature study techniques. Furthermore, the collected data is analyzed using a descriptive method to provide an in-depth and systematic explanation. The results of this study show that there are still many Deputy Ministers who hold dual positions in the SOE sector. The non-compliance of the Deputy Ministers shows arrogance and abuse of power in exercising their authority. Of course, this is contrary to existing regulations and mandates from the Constitution.